Preparation method of superfine ceramic powder modified C / C-SiC-ZrC composite material
Through the introduction of ultra-fine ceramic powder inside the C/C porosity and using a melting seepage process to prepare the C/C-SIC-ZRC composite material, it solves the problem of insufficient performance in existing materials in ultra-high temperature environments, and realized more. Excellent ablation performance.
Patent Information
- Application Number
- CN202310922841.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-01-28
AI Technical Summary
The existing C/C-SiC-ZrC composites have insufficient ablation performance in ultra-high temperature environments and cannot meet the strict requirements of supersonic aircraft.
The melting seepage process is used to introduce ultra-fine ceramic powder inside C/C's porous body to prepare a C/C-SIC-ZRC composite material composed of SIC+ZRC+ultra-fine ceramic phase.
Improve the antioxidant performance and resistance of composite materials, show excellent ablation performance, and significantly decreased quality ablation rates and line ablation rates.
Smart Images

Figure CN119371223A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of design and preparation of thermal protective materials, and specifically relates to a preparation method and application of an ultrafine ceramic powder modified C / C-SiC-ZrC composite material. Background Art
[0002] The rapid development of hypersonic vehicles has put forward extremely stringent requirements on high-temperature thermal protection materials. In these environments, high-temperature thermal protection materials not only need to withstand higher temperatures (≥2000℃) and longer service time (≥3000s), but also need to withstand the erosion of high-speed airflow and the corrosion of oxidizing gases. Existing C / C composites and C / C-SiC composites are limited by heat resistance and can no longer meet the use requirements of components such as hypersonic vehicle nose cones, wing leading edges, and long-life engine combustion chambers, which to a certain extent restricts their application in the ultra-high temperature field. C / C-SiC-ZrC composites prepared by matrix modification of porous C / C composites using ZrC and SiC ceramics are one of the most widely used thermal protection materials. As near-space vehicles develop towards ultra-high Mach, the surface ablation temperature of conventional C / C-SiC-ZrC composites is getting higher and higher during service, and the ablation environment is becoming more and more harsh. Therefore, how to improve the ablation performance of C / C-SiC-ZrC composites has become a major research hotspot.
[0003] The preparation methods of traditional modified C / C-SiC-ZrC composite materials mainly include precursor impregnation cracking method or combined reaction infiltration method. This type of preparation process is complicated, the preparation cycle is long, and the selection range of reactants is limited due to reaction conditions. For example, patent CN116178051A discloses a method for preparing a rare earth oxide modified C / C-SiC-ZrC composite material. The method adopts the PIP process to prepare a rare earth oxide modified C / C-SiC-ZrC composite material, specifically: polycarbozirconium and polycarbosilane precursor solutions and rare earth nitrate solutions are alternately introduced into the porous C / C-SiC composite material, and after multiple curing-cracking, a rare earth oxide modified C / C-SiC-ZrC composite material is prepared. The resulting product is ablated at 2100°C oxyacetylene for 600s, 200s per time, and the linear ablation rate is 2.33°C oxyacetylene. Patent CN114133259A discloses a method for preparing a resin-modified C / C-SiC-ZrC composite material, comprising the following steps: (1) using a CVI process to deposit a pyrolytic carbon interface / matrix in a carbon fiber preform to obtain a porous C / C composite material; (2) using a CVI process to deposit a SiC matrix in the porous C / C composite material to obtain a porous C / C-SiC composite material; (3) preparing a modified precursor; (4) using a PIP process to introduce the modified precursor solution into the porous C / C-SiC composite material, and after multiple curing-cracking, a C / C-SiC-ZrC composite material is prepared. However, this patent does not involve ablation resistance. Patent CN112358307A discloses a method for preparing a C / C-SiC-ZrC composite material, which comprises the following steps: (1) subjecting the mesophase pitch carbon fiber to primary carbonization to obtain carbon fiber I, and then subjecting the carbon fiber I to secondary carbonization to obtain carbon fiber II, weaving the carbon fiber II into carbon cloth, and then using a fine weaving puncture method to puncture the carbon cloth in the Z direction using PAN-based carbon fiber to obtain a porous C / C skeleton I; (2) subjecting the porous C / C skeleton I to primary graphitization, and then using a pyrolysis carbonization method to densify the porous C / C skeleton I to obtain a porous C / C skeleton II; (3) subjecting the porous C / C skeleton II to secondary graphitization to obtain a porous C / C skeleton III, and then using an impregnation pyrolysis method to densify the porous C / C skeleton III to obtain the three-dimensional C / C-Si C-ZrC composite material; the precursor solution used in the impregnation pyrolysis method is an organic solution including an inorganic zirconium source and an organic silicon source. The linear ablation rate of the obtained product is less than 1.2×10 -3 mm / s, mass ablation rate is less than 1×10 -4 g / s. The surface temperature of the composite material obtained in Example 2 after plasma ablation at 2000°C is 236°C lower than that of the C / C-SiC-ZrC composite material prepared from ordinary PAN-based carbon fiber. After ablation for 360s, the linear ablation rate is 0.82×10-3 mm / s.
[0004] A search revealed that there are few records so far of preparing sinter-resistant C / C-SiC-ZrC composite materials by melt infiltration process using appropriate amounts of ultrafine ceramic powder, silicon powder, zirconium powder or Zr-Si alloy. Summary of the invention
[0005] In order to overcome the defects of the above-mentioned prior art, the present invention proposes for the first time to use a melt infiltration process to prepare a C / C-SiC-ZrC composite material modified with ultrafine ceramic powders having excellent ablation resistance. The present invention has the advantages of simple process, short preparation cycle, low cost, etc., and through this method, various types of ultrafine ceramic powders can be introduced into the C / C porous body. At the same time, the obtained ultrafine ceramic powder modified C / C-SiC-ZrC composite material has good antioxidant and ablation resistance.
[0006] The technical solution adopted to achieve the purpose of the present invention is: to provide an ultrafine ceramic powder modified C / C-SiC-ZrC composite material, which is composed of carbon fiber, a carburized layer, a SiC and ZrC matrix and an ultrafine ceramic phase, wherein the carburized layer is coated on the carbon fiber, and the ceramic phase composed of SiC, ZrC and an ultrafine ceramic phase is coated on the C matrix, wherein SiC and ZrC are generated in situ, and the ultrafine ceramic phase is uniformly distributed inside the ceramic matrix composed of SiC and ZrC; the ultrafine ceramic phase is directly introduced into the composite material by melt infiltration; the C matrix is composed of a carbon fiber blank and a carburized layer attached to the surface of the carbon fiber blank.
[0007] In the composite material, the volume fraction of the carbon fiber is 20-45%, preferably 20%-40%, and more preferably 20%-30%.
[0008] In the composite material, the volume fraction of the carbon-increasing layer is 10-40%, preferably 15-40%, and more preferably 15-30%.
[0009] In the composite material, the volume fraction of the SiC and ZrC matrix is 1-35%, preferably 10-35%, and more preferably 15-25%.
[0010] In the composite material, the volume fraction of the ultrafine ceramic phase is 1-15%, preferably 2-10%.
[0011] The SiC+ZrC+ultrafine ceramic phase of the present invention may account for 2-50% of the volume of the composite material, preferably 10-45%, and more preferably 12-45%.
[0012] The equivalent particle size of the ultrafine ceramic phase is 10-5000 nm, preferably 500-3000 nm, and more preferably 500-1000 nm. In the present invention, the equivalent particle size refers to the diameter of the ultrafine ceramic phase after being converted into a sphere of equal volume.
[0013] The present invention also provides a method for preparing an ultrafine ceramic powder modified C / C-SiC-ZrC ceramic matrix composite material, which is characterized by comprising the following steps in order:
[0014] 1) A carbon fiber reinforced structure is prepared by molding short fibers, laminating long fiber fabrics, needle punching or multi-dimensional weaving / puncturing to obtain a carbon fiber preform, and then a carbonized layer is obtained by liquid phase impregnation-carbonization (LIC), chemical vapor deposition (CVI), liquid phase vapor deposition (CLVI) or a composite process of CVI and LIC, followed by high temperature graphitization treatment under a protective atmosphere to obtain a densified C / C porous green body.
[0015] 2) mixing Si powder, Zr powder and ultrafine ceramic powder, ball milling and drying to obtain a mixed powder; in step 2), the molar ratio of Si powder: Zr powder: ultrafine ceramic powder is 6-9: 1-4: 0.1-1.5;
[0016] 3) Using the embedding method, the graphitized C / C porous body is covered with mixed powder.
[0017] Or use the powder metallurgy pressing method to put the pressed mixed powder and C / C porous green body into a graphite tank,
[0018] Under a protective atmosphere, the temperature is raised to the infiltration temperature, kept warm, and then cooled to room temperature to obtain a C / C-SiC-ZrC composite material modified with ultrafine ceramic powder. The infiltration temperature is 1700°C-2200°C, and the holding time at the infiltration temperature is greater than or equal to 0.5h.
[0019] Preferably, the density of the carbon fiber preform in step 1) is 0.2 g / cm 3 -1.0g / cm 3 .
[0020] As a further preference, the density of the carbon fiber preform in step 1) is 0.4 g / cm 3 -0.8g / cm 3 .
[0021] The carbon-enhanced layer can be pyrolytic carbon, asphalt carbon or resin carbon, preferably pyrolytic carbon.
[0022] Preferably, the density of the C / C porous body obtained after graphitization in step 1) is 0.6 g / cm 3 -1.7g / cm 3 .
[0023] As a further preference, the density of the C / C porous body obtained after graphitization in step 1) is 1.2 g / cm 3 -1.6g / cm 3 .
[0024] Preferably, the temperature of the graphitization treatment in step 1) is 1800-2400°C.
[0025] As a further preference, the temperature of the graphitization treatment in step 1) is 1800-2200°C.
[0026] Preferably, the time of graphitization treatment in step 1) is 1-3 hours.
[0027] Preferably, in step 2), the molar ratio of Si powder: Zr powder: ultrafine ceramic powder is 6-9: 1-3: 0.4-1.5.
[0028] Preferably, the grinding balls used in step 2) are ZrO2 or WC balls.
[0029] Preferably, in step 2), the ball milling time is 12-48 h, the ball milling speed is 100-250 r / min, and the mass ratio of ball mill to powder is 2-10:1.
[0030] As a further preference, in step 2), the ball milling time is 24-36 h, the ball milling speed is 100-180 r / min, and the mass ratio of ball mill to powder is 4-6:1.
[0031] Preferably, in step 3), the mass ratio of C / C porous body to mixed powder is 1:2-4.
[0032] Preferably, the heating rate of the infiltration process in step 3) is 5-20°C / min, more preferably 10-15°C / min.
[0033] Preferably, the infiltration temperature in step 3) is 1700°C-2000°C.
[0034] Preferably, the infiltration time in step 3) is 0.5-4 h, more preferably 1.5-4 h.
[0035] Preferably, the cooling rate after the infiltration in step 3) is 5-20°C / min, preferably 5-15°C / min.
[0036] The ultrafine ceramic powder particles are selected from at least one of carbides, borides, nitrides, oxides, medium (high) entropy ceramic powders and the like.
[0037] The purity of the Si powder, Zr powder and ultrafine ceramic powder is greater than or equal to 99%, the particle size of the Si powder and Zr powder is -80 mesh, and the particle size of the ultrafine ceramic powder is 10-5000nm, preferably 500-3000nm, and more preferably 500-1000nm.
[0038] In the present invention, Zr is prone to violently react with C during the infiltration process at high temperature, damaging the carbon fiber and the carburized layer, resulting in a rapid decline in product performance. Therefore, it is necessary to strictly control the infiltration temperature (lower temperatures limit the melt entry, which is not conducive to material densification, and higher temperatures cause violent reactions between metal powder and C, damaging the internal structure of the material), the ratio of Zr powder, Si powder and ultrafine ceramic phase, the particle size of the ultrafine ceramic phase, the vacuum degree in the furnace during the infiltration process, and other parameters.
[0039] The density of the ultrafine ceramic powder modified C / C-SiC-ZrC composite material is 2.0-2.8 g / cm 3 .
[0040] The C matrix consists of a carbon fiber blank and a carbon-enhanced layer attached to the surface of the carbon fiber blank.
[0041] After carburizing, a carbon fiber blank forms a carburized layer on its surface.
[0042] The ultrafine ceramic powder modified C / C-SiC-ZrC composite material developed and prepared by the present invention can be used for thermal protection components. After optimization, the ultrafine ceramic powder modified C / C-SiC-ZrC composite material developed and prepared by the present invention was subjected to plasma ablation experiments. It was found that the mass ablation rate and line ablation rate could be as low as 0.02 mg / s and 3×10 -5 mm / s. Its performance is better than existing products.
[0043] When preparing the ultrafine ceramic powder modified C / C-SiC-ZrC composite material, the reaction raw materials are ball-milled to homogenize the mixed powder. At the same time, the melt infiltration conditions are controlled so that the ultrafine ceramic phase can be homogenized before entering the C / C porous body along with the melt containing Zr and Si. The particle size of the ultrafine ceramic powder is preferably within a suitable range. If it is too small, agglomeration will easily occur after introduction. If it is too large, it will not easily enter the porous body or block the capillaries inside the C / C porous body, resulting in excessive porosity of the composite material and affecting the material performance.
[0044] Advantages and technical effects
[0045] 1. The process of adding components is simple, and components that cannot enter the interior of the C / C porous body through the precursor impregnation and cracking method can be added, which broadens the selection range of modified components.
[0046] 2. Multiple components can be added directly according to demand, which broadens the material's ablation resistance temperature range.
[0047] 3. The generated composite material has excellent density and each phase is evenly distributed.
[0048] 4. The improved reaction infiltration method has a short preparation cycle, simple preparation process, low cost, and can meet large-scale production applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Attached Figure 1 This is a cross-sectional microscopic morphology of the composite material prepared in Example 1 after polishing.
[0050] Attached Figure 2 This is the macroscopic ablation morphology of the composite material prepared in Example 1.
[0051] Attached Figure 3 This is the macroscopic ablation morphology of the composite material prepared in Comparative Example 1.
[0052] Attached Figure 4 This is the macroscopic ablation structure of the composite material prepared in Comparative Example 2.
[0053] from Figure 1 It can be seen that SiC and ZrC in the composite material prepared in Example 1 are formed on the surface of the C matrix and effectively wrap the C matrix. The added ZrC ultrafine powder infiltrates with the Zr and Si melts and is dispersed to fill the excess pores, thereby playing a role of dispersion strengthening for the composite material.
[0054] from Figure 2 , Figure 3 It can be seen that the ultrafine powder modified C / C-SiC-ZrC composite material (Example 1, ablation temperature of 2000°C) obtained by infiltrating a mixed powder of Zr, Si and ZrC ultrafine powder into a C / C blank using the RMI process has better ablation performance than the C / C-SiC-ZrC composite material prepared from pure Zr and Si mixed powder (Comparative Example 1, ablation temperature of 1900°C). The white layer on its surface is the ZrO2 layer obtained after ablation. Large ablation pits appear on the surface of Comparative Example 1. This is because Zr reacts violently with carbon fiber during the infiltration process, damaging the carbon fiber, and a large amount of SiO2 volatilizes during the ablation process. This shows that the addition of ultrafine ceramic powder is beneficial to the improvement of the ablation performance of C / C-SiC-ZrC composite materials.
[0055] from Figure 4It can be seen that if too much ultrafine powder is added by the reactive infiltration process, the viscosity of the Zr and Si melts will decrease, resulting in a decrease in the total amount of melt entering the C / C porous body, and the porosity of the modified C / C-SiC-ZrC composite material will decrease. During the ablation process, the flame may directly enter the interior of the composite material and damage the carbon fiber, and its ablation performance will be greatly reduced. DETAILED DESCRIPTION
[0056] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0057] Example 1
[0058] 1) The carbon fiber reinforced structure is prepared by molding short fibers, laminating long fiber fabrics or multi-dimensional weaving / puncturing to obtain a carbon fiber preform, and then pyrolytic carbon is deposited by chemical vapor infiltration, followed by high-temperature graphitization treatment under a protective atmosphere to obtain a graphitized C / C porous body. The density of the carbon fiber preform is 0.8 g / cm 3 The density of the C / C porous body obtained after graphitization is 1.6 g / cm 3 The temperature of high temperature graphitization treatment is 2200°C and the time is 2h. Then the composite material is dried in low temperature vacuum for use in subsequent steps.
[0059] 2) Si powder, Zr powder and ultrafine ZrC powder with a purity of more than 99% are mixed, ball-milled and dried to obtain a mixed powder, wherein the molar ratio of Si powder: Zr powder: ultrafine ZrC is 7:3:0.4, the ball milling medium is ZrO2, the ball-to-material mass ratio is 5:1, the ball milling speed is 180r / min, and the time is 24h.
[0060] 3) The graphitized C / C porous body is covered with mixed powder by an embedding method, heated and kept warm for a period of time under a protective atmosphere, and then cooled to room temperature to obtain a C / C-SiC-ZrC composite material modified with ultrafine ZrC ceramic powder.
[0061] Among them, the mass ratio of C / C porous green body and mixed powder is 1:3, the heating rate of the infiltration process is 10°C / min, the holding temperature of the infiltration process is 1700°C, the holding time of the infiltration process is 4h, and the cooling rate of the infiltration process is 15°C / min.
[0062] The above preparation process can obtain a density range of 2.20g / cm 3 -2.40g / cm 3The C / C-SiC-ZrC composite material modified by ultrafine ZrC ceramic powder between 2000 and 2000 μm was prepared. After 150 s of spark plasma ablation, the ablation temperature of the composite material reached 2000 °C, and the surface was relatively flat without ablation pits. The mass ablation rate and line ablation rate were 0.05 mg / s and 4×10 -4 mm / s. In comparison with modified C / C-SiC-ZrC composites of the same density, the composite material exhibits better ablation performance in the ablation test.
[0063] Example 2
[0064] 1) The 2.5D carbon fiber preform woven with carbon fibers is deposited with pyrolytic carbon by chemical vapor infiltration, and then subjected to high-temperature graphitization treatment under a protective atmosphere to obtain a C / C porous green body after pyrolytic carbon deposition. The density of the carbon fiber preform is 0.5 g / cm 3 The density of the C / C porous body obtained after deposition is 1.5 g / cm 3 The temperature of high temperature graphitization treatment is 1800°C and the time is 2h. Then the composite material is dried in low temperature vacuum for use in subsequent steps.
[0065] 2) Si powder, Zr powder, HfC and LaB6 ultrafine ceramic powders with a purity of more than 99% are mixed, ball-milled and dried to obtain a mixed powder. The molar ratio of Si powder: Zr powder: HfC: LaB6 is 9:1:0.5:0.4, the ball milling medium is ZrO2, the ball-to-material mass ratio is 4:1, the ball milling speed is 100 r / min, and the time is 36 hours.
[0066] 3) The C / C porous green body after pyrolytic carbon deposition is covered with mixed powder by an embedding method, heated and kept warm for a period of time under a protective atmosphere, and then cooled to room temperature to obtain a C / C-SiC-ZrC composite material modified with ultrafine HfC and LaB6 ceramic powders.
[0067] Among them, the mass ratio of C / C porous green body: mixed powder is 1:2.5, the heating rate of the infiltration process is 15°C / min, the holding temperature of the infiltration process is 2000°C, the holding time of the infiltration process is 1.5h, and the cooling rate of the infiltration process is 5°C / min.
[0068] The above preparation process can obtain a density range of 2.30g / cm 3 -2.50g / cm 3The C / C-SiC-ZrC composite material modified by ultrafine ZrC and LaB6 ceramic powder. After 180s of electric spark plasma ablation, the ablation temperature of the composite material reached 2000℃, and the surface was relatively flat without ablation pits. The mass ablation rate and line ablation rate were 0.02mg / s and 3×10 -5 mm / s. In comparison with modified C / C-SiC-ZrC composites of the same density, the composite material exhibits better ablation performance in the ablation test.
[0069] Example 3
[0070] 1) The carbon fiber reinforced structure is prepared by molding short fibers, laminating long fiber fabrics or multi-dimensional weaving / puncturing to obtain a carbon fiber preform, and then a carbonized layer is obtained by a CVI and LIC composite process, followed by high-temperature graphitization treatment under a protective atmosphere to obtain a graphitized C / C porous body; wherein the density of the carbon fiber preform is 0.7 g / cm 3 The density of the C / C porous body obtained after graphitization is 1.6 g / cm 3 The graphitization temperature is 2000°C and the time is 2h. The composite material is then vacuum dried at low temperature for use in subsequent steps.
[0071] 2) Si powder, Zr powder and HfC ultrafine ceramic powder with a purity of more than 99% are mixed, ball-milled and dried to obtain a mixed powder, wherein the molar ratio of Si powder: Zr powder: HfC is 6:2:1.5, the ball milling medium is ZrO2, the ball-to-material mass ratio is 4:1, the ball milling speed is 100 r / min, and the time is 36 hours.
[0072] 3) The graphitized C / C porous body is covered with the mixed powder by an embedding method, heated and kept warm for a period of time under a protective atmosphere, and then cooled to room temperature to obtain a C / C-SiC-ZrC composite material modified with ultrafine HfC ceramic powder.
[0073] Among them, the mass ratio of C / C porous green body: mixed powder is 1:2.5, the heating rate of the infiltration process is 15°C / min, the holding temperature of the infiltration process is 2000°C, the holding time of the infiltration process is 1.5h, and the cooling rate of the infiltration process is 10°C / min.
[0074] The above preparation process can obtain a density range of 2.30g / cm 3 -2.50g / cm 3The C / C-SiC-ZrC composite material modified by ultrafine HfC ceramic powder. After 180s of spark plasma ablation, the ablation temperature of the composite material reached 2000℃, and the surface was relatively flat without ablation pits. The mass ablation rate and line ablation rate were 0.05mg / s and 1×10 -4 mm / s. In comparison with modified C / C-SiC-ZrC composites of the same density, the composite material exhibits better ablation performance in the ablation test.
[0075] Comparative Example 1
[0076] 1) The carbon fiber reinforced structure is prepared by molding short fibers, laminating long fiber fabrics or multi-dimensional weaving / puncturing to obtain a carbon fiber preform, and then a carbonized layer is obtained by a CVI and LIC composite process, followed by a high-temperature graphitization treatment under a protective atmosphere to obtain a graphitized C / C porous body. The density of the carbon fiber preform is 0.7 g / cm 3 The density of the C / C porous body obtained after graphitization is 1.5 g / cm 3 The heat treatment temperature is 2200°C and the time is 2h. The composite material is then vacuum dried at low temperature for use in subsequent steps.
[0077] 2) The Si powder and Zr powder with a purity greater than 99% are ball-milled and dried to obtain a mixed powder, wherein the molar ratio of Si powder to Zr powder is 7:3, the ball milling medium is ZrO2, the ball-to-material mass ratio is 5:1, the ball milling speed is 180 r / min, and the time is 24 h.
[0078] 3) The C / C porous body after graphitization is covered with the mixed powder by an embedding method, heated and kept warm for a period of time under a protective atmosphere, and then cooled to room temperature to obtain a C / C-SiC-ZrC composite material.
[0079] Among them, the mass ratio of C / C porous green body and mixed powder is 1:3, the heating rate of the infiltration process is 10°C / min, the holding temperature of the infiltration process is 1700°C, the holding time of the infiltration process is 4h, and the cooling rate of the infiltration process is 15°C / min.
[0080] The density range obtained by the above preparation process is 2.10g / cm 3 -2.30g / cm 3 C / C-SiC-ZrC composite material. After 90s of spark plasma ablation, the ablation temperature of the composite material reached 1900℃, and large ablation pits appeared on the surface. The mass ablation rate and line ablation rate were 11.7mg / cm 3 and 26.7 mm / s, the ablation performance needs to be improved.
[0081] Comparative Example 2
[0082] 1) The carbon fibers are woven or laminated to prepare a reinforcement structure to obtain a carbon fiber preform, and then pyrolytic carbon is deposited by chemical vapor infiltration, followed by high-temperature graphitization treatment under a protective atmosphere to obtain a C / C porous body after pyrolytic carbon deposition. The density of the carbon fiber preform is 0.6 g / cm 3 The chemical vapor deposition time is 80 h, and the density of the C / C porous body obtained after deposition is 1.3 g / cm 3 The heat treatment temperature is 2100°C and the time is 2h. The composite material is then vacuum dried at low temperature for use in subsequent steps.
[0083] 2) Si powder, Zr powder and ZrC ultrafine nano ceramic powder with a purity of more than 99% are mixed, ball-milled and dried to obtain a mixed powder, wherein the molar ratio of Si powder: Zr powder: ZrC is 6:4:3, the ball milling medium is ZrO2, the ball-to-material ratio is 10:1, the ball milling speed is 50r / min, and the time is 48h.
[0084] 3) The C / C porous green body after pyrolytic carbon deposition is covered with mixed powder by an embedding method, heated and kept warm for a period of time under a protective atmosphere, and then cooled to room temperature to obtain a C / C-SiC-ZrC composite material modified with ultrafine nano ZrC ceramic powder.
[0085] Among them, the mass ratio of C / C porous green body: mixed powder is 1:4, the heating rate of the infiltration process is 20°C / min, the holding temperature of the infiltration process is 2300°C, the holding time of the infiltration process is 0.5h, and the cooling rate of the infiltration process is 10°C / min.
[0086] The porosity of the modified composite material obtained by the above preparation process is about 15%-20%. A dense structure cannot be formed inside the material, and the inside of the material cannot be effectively protected during the ablation process. After 60s of electric spark plasma ablation, the ablation temperature of the composite material reaches 1800°C, and large ablation pits appear on the surface. The mass ablation rate and line ablation rate are 17.7mg / s and 30.5mm / s respectively, and the ablation performance is extremely poor.
[0087] Comparative Example 3
[0088] 1) The 2.5D carbon fiber preform woven with carbon fibers is subjected to pyrolytic carbon deposition by chemical vapor infiltration, followed by high-temperature graphitization treatment under a protective atmosphere to obtain a C / C porous green body after pyrolytic carbon deposition. The density of the carbon fiber preform is 0.7 g / cm 3 The chemical vapor deposition time is 170 h, and the density of the C / C porous body obtained after deposition is 1.6 g / cm 3The heat treatment temperature is 2000°C and the time is 2h. The composite material is then vacuum dried at low temperature for use in subsequent steps.
[0089] 2) Si powder, Zr powder and HfC ultrafine ceramic powder with a purity of more than 99% are mixed, ball-milled and dried to obtain a mixed powder, wherein the molar ratio of Si powder: Zr powder: HfC is 6:2:1.5, the ball milling medium is ZrO2, the ball-to-material ratio is 4:1, the ball milling speed is 100 r / min, and the time is 36 hours.
[0090] 3) The C / C porous green body after pyrolytic carbon deposition is covered with mixed powder by an embedding method, heated and kept warm for a period of time under a protective atmosphere, and then cooled to room temperature to obtain a C / C-SiC-ZrC composite material modified with ultrafine HfC ceramic powder.
[0091] Among them, the mass ratio of C / C porous green body: mixed powder is 1:2.5, the heating rate of the infiltration process is 3°C / min, the holding temperature of the infiltration process is 2400°C, the holding time of the infiltration process is 2.5h, and the cooling rate of the infiltration process is 30°C / min.
[0092] The C / C-SiC-ZrC composite material modified by the ultrafine HfC ceramic powder obtained by the above preparation process has a large porosity. After 60s of spark plasma ablation, the ablation temperature of the composite material reached 2000℃, and large ablation pits appeared on the surface. The bottom of the material was severely oxidized, and its mass ablation rate and line ablation rate were 30mg / s and 32mm / s respectively, and the ablation performance was extremely poor.
Claims
1. An ultrafine ceramic powder modified C / C-SiC-ZrC composite material, characterized in that: The composite material consists of carbon fiber, a carburized layer, a SiC and ZrC matrix and an ultrafine ceramic phase, wherein the carburized layer is coated on the carbon fiber, and the ceramic phase composed of SiC, ZrC and an ultrafine ceramic phase is coated on the C matrix, wherein SiC and ZrC are generated in situ, and the ultrafine ceramic phase is uniformly distributed inside the ceramic matrix composed of SiC and ZrC; the ultrafine ceramic phase is directly introduced into the composite material by melt infiltration; and the C matrix consists of a carbon fiber blank and a carburized layer attached to the surface of the carbon fiber blank.
2. The ultrafine ceramic powder modified C / C-SiC-ZrC composite material according to claim 1, characterized in that: In composite materials, The volume fraction of the carbon fiber is 20-45%, preferably 20%-40%, and more preferably 20%-30%; The volume fraction of the carbon-added layer is 10-40%, preferably 15-40%, and more preferably 15-30%; The volume fraction of the SiC and ZrC matrix is 1-35%, preferably 10-35%, and more preferably 15-25%; The volume fraction of the ultrafine ceramic phase is 1-15%, preferably 2-10%.
3. The ultrafine ceramic powder modified C / C-SiC-ZrC composite material according to claim 2, characterized in that: In composite materials, The SiC+ZrC+ultrafine ceramic phase accounts for 2-50%, preferably 10-45% of the volume of the composite material.
4. The ultrafine ceramic powder modified C / C-SiC-ZrC composite material according to claim 2, characterized in that: The equivalent particle size of the ultrafine ceramic phase is 10-5000 nm, preferably 500-3000 nm, and more preferably 500-1000 nm.
5. A method for preparing the ultrafine ceramic powder modified C / C-SiC-ZrC ceramic matrix composite material according to any one of claims 1 to 4, characterized in that The steps include: 1) The carbon fiber reinforced structure is prepared by molding short fibers, laminating long fiber fabrics or multi-dimensional weaving / puncturing to obtain a carbon fiber preform, and then a carbon layer is obtained by liquid phase impregnation-carbonization (LIC), chemical vapor deposition (CVI), liquid phase vapor deposition (CLVI) or a composite process of CVI and LIC, followed by high-temperature graphitization treatment under a protective atmosphere to obtain a dense C / C porous green body; 2) Si powder, Zr powder and ultrafine ceramic powder are mixed, ball-milled and dried to obtain a mixed powder; in step 2), the molar ratio of Si powder: Zr powder: ultrafine ceramic powder is 6-9: 1-4: 0.1-1.5; 3) Using the embedding method, the graphitized C / C porous body is covered with mixed powder. Or use the powder metallurgy pressing method to put the pressed mixed powder and C / C porous green body into a graphite tank, Under a protective atmosphere, the temperature is raised to the infiltration temperature, kept warm, and then cooled to room temperature to obtain a C / C-SiC-ZrC composite material modified with ultrafine ceramic powder. The infiltration temperature is 1700°C-2200°C, and the holding time at the infiltration temperature is greater than or equal to 0.5h.
6. The method for preparing a superfine ceramic powder modified C / C-SiC-ZrC composite material according to claim 5, characterized in that: The density of the carbon fiber preform in step 1) is 0.2 g / cm 3 -1.0g / cm 3 ; In step 1), the carbon-increasing layer may be pyrolytic carbon, asphalt carbon or resin carbon; The density of the C / C porous body obtained after densification in step 1) is 0.6 g / cm 3 -1.7g / cm 3 ; The temperature of the graphitization treatment in step 1) is 1800-2400°C; Step 2) the molar ratio of Si powder: Zr powder: ultrafine ceramic powder is 6-9: 1-3: 0.4-1.5; Step 3) the mass ratio of C / C porous body to mixed powder is 1:2-4; In step 3), the infiltration temperature is 1700°C-2000°C, and the infiltration time is 0.5-4h.
7. The method for preparing a superfine ceramic powder modified C / C-SiC-ZrC composite material according to claim 5, characterized in that: The time of graphitization treatment in step 1) is 1-3 hours; The grinding balls used in step 2) are ZrO2 balls or WC balls; In step 2), the ball milling time is 12-48 hours, the ball milling speed is 100-250 r / min, and the ball milling mass ratio is 2-10:1; The heating rate of the infiltration process in step 3) is 5-20°C / min; The holding time of the infiltration process in step 3) is 0.5-4h; The cooling rate of the infiltration process in step 3) is 5-20°C / min; The ultrafine ceramic powder particles are selected from at least one of carbides, borides, nitrides, oxide ceramic powders, medium entropy ceramic powders, high entropy ceramic powders and the like.
8. The method for preparing a superfine ceramic powder modified C / C-SiC-ZrC composite material according to claim 5, characterized in that: The purity of the Si powder, Zr powder and ultrafine ceramic powder is greater than or equal to 99%, the particle size of the Si powder and Zr powder is -80 mesh, and the particle size of the ultrafine ceramic powder is 10-5000nm, preferably 500-3000nm, and more preferably 500-1000nm.
9. The method for preparing a superfine ceramic powder modified C / C-SiC-ZrC composite material according to claim 5, characterized in that: The density of the obtained ultrafine ceramic powder modified C / C-SiC-ZrC composite material is 2.0-2.8g / cm 3 .
10. An application of the ultrafine ceramic powder modified C / C-SiC-ZrC composite material according to any one of claims 1 to 4, characterized in that: The applications include use in heat protection components.
Citation Information
Patent Citations
Preparation method of three-dimensional high-thermal-conductivity C / C-SiC-ZrC composite material
CN112358307A
Preparation method of resin modified C / (C-) SiC-ZrC composite material
CN114133259A
Preparation method of rare earth oxide modified C / (C-) SiC-ZrC composite material
CN116178051A
C / C-SiC-ZrC-TiC composite material and preparation method thereof
CN104671814A
ZrC-TiC modified C / C-SiC composite material and preparation method thereof
CN104671815A